Synthesis of some new pyrazolylfuropyrimidinethiones and triazolofuropyrimidinethiones - Abdel-Hamid, Mohamed Abdel Megid; Elkazak, Azza Mohamed; Sead, Magdy Hamed; Mohamed, Osama Farouk (European Journal of Chemistry, 2012)
Some novel pyrazolylfuropyrimidinethiones were synthesized from cyclocondensation of 4-hydrazino-5,6-diphenylfuro [2,3-d] pyrimidine-2(1H)-thione (3) with different enaminones and 1,3-dicarbonyl compounds. Whereas the furotriazolo-pyrimidinethiones were synthesized from reaction of compound 3 with benzoyl chloride, p-chlorobenzaldehyde and carbon disulphide. Furthermore, furotetrazolo-pyrimidinethione and ditetrazolofuro pyrimidine were synthesized.